2013
DOI: 10.1371/journal.pone.0059689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 3D Microenvironment on Phenotype, Gene Expression, and EGFR Inhibition of Colorectal Cancer Cell Lines

Abstract: Three-dimensional (3D) tumor cell cultures grown in laminin-rich-extracellular matrix (lrECM) are considered to reflect human tumors more realistic as compared to cells grown as monolayer on plastic. Here, we systematically investigated the impact of ECM on phenotype, gene expression, EGFR signaling pathway, and on EGFR inhibition in commonly used colorectal cancer (CRC) cell lines. LrECM on-top (3D) culture assays were performed with the CRC cell lines SW-480, HT-29, DLD-1, LOVO, CACO-2, COLO-205 and COLO-206… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

20
242
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 305 publications
(275 citation statements)
references
References 30 publications
20
242
0
13
Order By: Relevance
“…33 For example, Luca et al noted that among the CRC cell lines they tested, those derived from metastatic cells formed grape-like morphology in lrECM matrix, whereas CRC cell lines established from primary tumor tissue formed mass spheroid morphology. 29 They also found that spheroid morphology did not correlate with the migratory, invasive, or proliferative capacity of CRC cell lines. Hongisto et al 33 reported that the JIMT1 breast cancer cell line formed mass-shaped spheroids on both Matrigel and polyHEMA (poly(2-hydroxyethyl methacrylate)) matrix, but more uniformly shaped and sized spheroids on Matrigel were observed, while more single cells mixed with larger structures appeared on polyHEMA.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…33 For example, Luca et al noted that among the CRC cell lines they tested, those derived from metastatic cells formed grape-like morphology in lrECM matrix, whereas CRC cell lines established from primary tumor tissue formed mass spheroid morphology. 29 They also found that spheroid morphology did not correlate with the migratory, invasive, or proliferative capacity of CRC cell lines. Hongisto et al 33 reported that the JIMT1 breast cancer cell line formed mass-shaped spheroids on both Matrigel and polyHEMA (poly(2-hydroxyethyl methacrylate)) matrix, but more uniformly shaped and sized spheroids on Matrigel were observed, while more single cells mixed with larger structures appeared on polyHEMA.…”
mentioning
confidence: 98%
“…A variety of cell lines showed reduced proliferation rate in 3D cultures compared to those cultured in 2D. 17,[27][28][29][30][31] 33 But interestingly, the same cell line cultured on the synthetic poly(2-hydroxyethylmethacrylate) (polyHEMA) 3D scaffold, exhibited a proliferation rate that was 7.2-fold slower than in 2D culture, 33 which suggests that the cell proliferation rate is also related to the type of 3D model in which the cells are cultured. In general, the proliferation rate of cells grown in 3D culture better represent the growth of tumors in vivo compared to those cultured in an unnatural 2D environment.…”
mentioning
confidence: 99%
See 3 more Smart Citations